A systematic mapping study of security, trust and privacy in clouds - Isaac Odun-Ayo; Toro-Abasi Williams; Jamaiah Yahaya (Bulletin of Electrical Engineering and Informatics, 2021)
Cloud computing thrives around trust and security in the relationship between cloud providers and users of their services. The objective was the conduct of a systematic mapping study of cloud computing security, trust and privacy. The research was executed using three classes of facets, namely topic, contribution, and research based on the systematic mapping process. The result shows that privacy issues and challenges on metric had 4.76% of the publications. On cloud trust in the domain of tool, the publications were 8.75%. The publications on design within the domain of model stood at 12.38%, and publications on privacy issues and challenges in the area of process were 8.57%. Furthermore, there were more articles published on privacy issues and challenges within the domain of evaluation research with 10.43%. The publications on design based on validation research made up 7.83% of the study. More papers were also published on frameworks and techniques within the domain of solution research with 5.22% each. There were more articles published on privacy issues and challenges with regards to philosophical research with 4.35%. Shortcomings in the fields of security, trust and privacy in the cloud, were identified through this study, which should motivate further research.